Lanthanide-based bis-(3, 5-dicarboxy-phenyl)terephthalamide metal–organic frameworks: slow relaxation of magnetization and detection of trace Fe2+ and Fe3+. Issue 16 (12th April 2021) - Lin, Qingfang; Xie, Wen; Zong, Zhihui; Liu, Zicheng; Sun, Yuqing; Liang, Lili
Abstract : [Dy2 (BDPT)1.5 (DMF)4 ]·H2 O n (1 ) and [Sm2 (BDPT)1.5 (DMF)4 ] n (2 ) were prepared with highly sensitive fluorescent detection of trace Fe 2+ and Fe 3+ . 1 exhibits weak antiferromagnetic interactions with signature of SMM behavior. Abstract : Solvothermal reactions of flexible aromatic linker bis(3, 5-dicarboxyphenyl)terephthalamide (H4 BDPT) with dysprosium and samarium salts yield two Ln-based metal–organic frameworks [Dy2 (BDPT)1.5 (DMF)4 ]·H2 O n (1 ) and [Sm2 (BDPT)1.5 (DMF)4 ] n (2 ) with inserted acylamide groups. Both 1 and 2 possess a 3D open framework built from 6-connecting Ln2 clusters and 4-connecting tetracarboxylate ligands. There are small 1-D helical channels in the structure occupying 29.8% of the framework. Magnetic measurements reveal that compound 1 exhibits weak antiferromagnetic interactions between Dy 3+ ions and a distinct slow relaxation phenomenon. The frequency-dependent ac susceptibility results reveal that 1 exhibits an χ M ′′ ac signal with observable maxima under 1500 Oe, indicating the signature of SMM behavior with the anisotropic barrier of 25 K and the pre-exponential factor τ 0 5.0 × 10 −7 s. Furthermore, both 1 and 2 serve as fluorescent probes for selectively detecting trace Fe 2+ and Fe 3+ through the luminescence emission quenching effect, with the detection limit of 1.03 × 10 −7 and 2.14 × 10 −7 M −1 for Fe 2+, respectively.